Detection and monitoring of fire and gas leakage systems in industries - Geetha, K; Prabha, P; Preetha Devi, C; Priyadharshini, S; Tamilselvan, S (International Journal of Engineering and Technology, 2018)
Now a days, Industries are more equipped with automatic system. Fire monitoring is one of the applications where continuous monitoring of temperature and humidity is essential to detect the fire in the industry. Fire detection is very much necessary to protect both the industry and to conserve environment and livelihood of human. This paper presents an algorithm to detect the fire in the industry based on ZigBee and GPRS wireless sensor network which provides low cost, low maintenance and good quality service when compared with the traditional method. The hardware circuitry of proposed solution is based on microcontroller, temperature sensor along with ZigBee and GPRS modules.